THE ROLE OF TONGKE-TONGKE VILLAGE GOVERNMENT IN IMPROVING SERVICE QUALITY AT THE VILLAGE OFFICE - Aulia, Fitri; Hidayat, Rahmat; Yusri (Program Studi Administrasi Publik, 2024)
Public services are a series of activities in order to fulfill service needs in accordance with those in the laws and regulations for every citizen and resident, or administrative services formed based on the law The existence of the Tongke - Tongke Village Office is expected to be able to provide the maximum to the people who come. However, the Tongke - Tongke Village Office has been maximized in providing public services to the community. This research aims to find out things descriptively about public services, which are located at the Tongke Village Office - Tongke Sinjai Regency. The results showed that the quality of public services was maximized. In the form of sufficient professionalism of employees in carrying out their duties. as well as existing facilities and infrastructure that are sufficient to support existing public services at the Tongke Village Office - Tongke, the existing services are quite good, therefore there is still a need for improvement by paying attention to the qualifications of employees in providing services. In terms of tangible (physical evidence), reliability (reliability), responsiveness (responsiveness), assurance (assurance), empathy (empathy). In addition, this research was conducted through literature studies or literature studies, in this study checking between libraries and paying attention to supervisory comments was carried out in order to maintain the immutability of the evaluation process, prevent and eliminate misinformation. So with the hope of improving the quality of public services that will be felt by the community. From this it will become a place of public service that has good performance by the community.